2020
DOI: 10.1371/journal.pone.0240264
|View full text |Cite
|
Sign up to set email alerts
|

Stimbiotic supplementation improved performance and reduced inflammatory response via stimulating fiber fermenting microbiome in weaner pigs housed in a poor sanitary environment and fed an antibiotic-free low zinc oxide diet

Abstract: This study investigated whether the inclusion of a stimbiotic (STB) can improve performance, influence intestinal microbiota and fermentation activity, and reduce pro-inflammatory cytokines in piglets fed a low zinc oxide diet without antimicrobial growth promotors compared to fructo-oligosaccharide (FOS) and mannan-oligosaccharide (MOS) when housed either in good sanitary (GS) or poor sanitary (PS) environments. One hundred forty-four male pigs (28-day-old) were sorted by initial body weight (BW) and allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
(59 reference statements)
3
32
0
Order By: Relevance
“…The XOS in this study was supplemented in low concentration that is not expected to produce sufficient SCFA, but the substantial increase in SCFA in response to XOS could be attributed to its priming of cecal microbiota for enhanced fermentation of selective substrates [ 1 ]. Recently, a term “stimbiotic” has been proposed to suggest the mechanism by which the oligosaccharides could influence the utilization of similar nutrients and their extraction from the diet by the gut microbiota [ 33 ]. It has been interpreted that while these oligosaccharides supplied in the diet or generated in situ in a small quantity are insufficient to contribute to a differentially high amount of SCFA production in the ceca of broilers, but it acts as a signaling molecule that stimulates the microbial adaptation to degrade dietary fiber sources [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The XOS in this study was supplemented in low concentration that is not expected to produce sufficient SCFA, but the substantial increase in SCFA in response to XOS could be attributed to its priming of cecal microbiota for enhanced fermentation of selective substrates [ 1 ]. Recently, a term “stimbiotic” has been proposed to suggest the mechanism by which the oligosaccharides could influence the utilization of similar nutrients and their extraction from the diet by the gut microbiota [ 33 ]. It has been interpreted that while these oligosaccharides supplied in the diet or generated in situ in a small quantity are insufficient to contribute to a differentially high amount of SCFA production in the ceca of broilers, but it acts as a signaling molecule that stimulates the microbial adaptation to degrade dietary fiber sources [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a specific strain of Ligilactobacillus salivarius was associated with increased clostridia and lactobacilli species as well as greater production of volatile fatty acids [ 19 ]. The use of symbiotics (a combination of probiotics with prebiotics) have also been shown to benefit fibrolytic bacteria, improving performancing and reducing inflammation in pigls [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in agreement with our findings, Yuan et al [ 32 ] also reported that the supplementation of XOS increased both acetate and butyrate in the ceca of broilers. In contrast with the effect of XOS3 on the ileal mucosa, its influence on the production of SCFA during the later growth phase of broilers infer to its ‘stimbiotic’ role on gut microbiota [ 33 ]. The variability in the fermentation characteristics of XOS could be reasonable because of the inconsistency in the composition of oligomer residues containing a different degree of polymerization.…”
Section: Discussionmentioning
confidence: 99%